Pengembangan Lembar Kerja Peserta Didik Elektronik (e-LKPD) Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI MIA SMAN 2 Parepare - Triana, Siti Hardiyanti; Danial, Muhammad; Salempa, Pince (Program Pasca Sarjana UNM, 2022)
This study is a development research, which aims at developing an electronic students worksheet based on guided inquiry on Acid-Base material which is valid, practical, and effective to be used to improve the learning outcomes. The research procedure employed ADDIE development model, which consisted of stages of analysis, design, devleopment, implementation, and evaluation. The electronic students worksheet was validated by two experts. Then, it was tested to grade XI MIA at SMAN 2 Parepare. The results of the study reveal that the electronic students worksheet developed is valid with the validity average 3.60. The practicality test covered: (1) learning implementation of electronic students worksheet based on guided inquiry is in the average M = 1.82 with fully implemented category, (2) the teacher gave positive response with the total average 91%, which means the electronic students worksheet is in very practical category, and (3) the students gave positive response with the total average 88.98, which is in very practical category. The electronic students worksheet based on guided inquiry developed has met the effective criteria as well with class completeness percentage 90.62%, meaning that it has over the class completeness percentage of 80% minimum. The electronic students worksheet developed consists of the cover, the title of material, electronic students worksheet manual, basic competence, competence achievement indicator, learning objective, and evaluation.